2008
DOI: 10.1900/rds.2008.5.73
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Incretins in Type 2 Diabetes: Role of GLP-1 Receptor Agonists and DPP-4 Inhibitors

Abstract: ■ AbstractUntil recently, the pathogenesis of type 2 diabetes mellitus (T2DM) has been conceptualized in terms of the predominant defects in insulin secretion and insulin action. It is now recognized that abnormalities in other hormones also contribute to the development of hyperglycemia. For example, the incretin effect, mediated by glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP), is attenuated in T2DM. Intravenous administration of GLP-1 ameliorates hyperglycemia in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 107 publications
(113 reference statements)
0
55
0
1
Order By: Relevance
“…It can be speculated that the longer duration of action of liraglutide, with respect to exenatide, could allow a more accurate control of post-prandial hyperglycaemia throughout the day; however, little data is available on the effects of liraglutide on glycaemic profile to draw any conclusion on this point. It has been reported that liraglutide has a lower immunogenicity than exenatide, with a reduced incidence of antibody formation (18); it is possible that high titres of specific antibodies could interfere with the efficacy of GLP-1 receptor agonists (19).…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that the longer duration of action of liraglutide, with respect to exenatide, could allow a more accurate control of post-prandial hyperglycaemia throughout the day; however, little data is available on the effects of liraglutide on glycaemic profile to draw any conclusion on this point. It has been reported that liraglutide has a lower immunogenicity than exenatide, with a reduced incidence of antibody formation (18); it is possible that high titres of specific antibodies could interfere with the efficacy of GLP-1 receptor agonists (19).…”
Section: Discussionmentioning
confidence: 99%
“…19,20) Because of its pleiotropic actions in nutrient homeostasis, GLP-1 is now under investigation as a potential treatment for patients with type 2 diabetes mellitus. Here we have demonstrated that a single oral ingestion of cinnamtannin A2, one of the tetrameric procyanidins, increased the GLP-1 secretion levels and insulin secretion in plasma without an oral glucose load ( Figs.…”
mentioning
confidence: 99%
“…Many of the drugs currently used for the treatment of type 2 diabetes, induce weight gain (sulphonylureas, thiazolidinediones, insulin). Incretin-based agents are weight-neutral or promote weight reduction [5][6][7][19][20][21][22]. ]…”
Section: Effect On Body Weightmentioning
confidence: 99%